Polyionic liquid gel adsorbent and method for adsorbing and separating gold, platinum and palladium
By introducing imidazole ring and Cardo structural fragments into the polyionic liquid gel adsorbent, a specific π-π conjugated structure and a high-stability network structure are formed, and the problems of poor selectivity for precious metal recycling and insufficient mechanical properties in the prior art are solved, and efficient combination of gold, platinum, palladium and high mechanical properties are achieved.
Patent Information
- Application Number
- CN202410301161.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-15
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-03-15
AI Technical Summary
The prior art has problems of poor selectivity and insufficient mechanical properties in precious metal recycling, making it difficult to effectively selectively recover gold, platinum, and palladium from complex metal solutions.
A polyion liquid gel adsorbent was designed. By introducing imidazole ring structural fragments and Cardo structural fragments on the molecular backbone, it forms a specific π-π conjugated structure and a high stability network structure, achieving high selective adsorption of gold, platinum and palladium, and having both high strength and high mechanical properties.
The adsorption rate of the polyion liquid gel adsorbent to gold, platinum and palladium is as high as 97%, and has high tensile strength and high mechanical properties. It can maintain good adsorption capacity in a high acid environment, solving the problems of poor selectivity and insufficient mechanical properties in the prior art.
Smart Images

Figure CN117983190B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorption and separation of gold, platinum and palladium, and in particular to a polyionic liquid gel adsorbent and a method for adsorbing and separating gold, platinum and palladium. Background Art
[0002] Precious metals play an important role in the wide application of high-tech industries such as mobile phones, computers, and automobiles. Due to the rapid renewal of these products, a large amount of industrial waste is generated. Since precious metal resources are limited and expensive around the world, efforts are being made to recover precious metals from secondary resources such as industrial waste. However, the selective recovery of precious metals, such as gold (III), platinum (IV), and palladium (II), from other metal ion solutions remains a challenge.
[0003] Ion exchange resin has a certain shape and good mechanical strength, and is a traditional adsorbent for adsorbing metal ions. However, due to the presence of hydrophobic polymer matrix in ion exchange resin and the low specific surface area of ion exchange resin, its adsorption capacity is limited. At the same time, its selectivity for metal ions is relatively poor, which limits its application in the precious metal industry.
[0004] In contrast, gel adsorbents have the advantages of porous network structure, high capacity and easy mass transfer. At the same time, functional monomers can be introduced into the gel adsorbent to enrich its performance. Ionic liquids are a class of organic salts that are completely composed of anions and cations and are usually liquid at room temperature. Polyionic liquid gel is a material that combines the functional advantages of ionic liquids and the three-dimensional network structure of gels. It can achieve high adsorption capacity while also achieving fast adsorption kinetics. Common cations in ionic liquids are protonated amino or quaternary ammonium salts, among which pyridine (especially 4-vinylpyridine) and imidazole are the most commonly used.
[0005] In recent years, the research on gel adsorbents has mainly focused on the molecular structure of imidazole-long carbon crosslinks. For example, Jian Yang (Separation of Gold (III) in Acidic Chloride Solution Using Porous Polymeric Ionic Liquid Gel, Journal of Chemical Engineering of Japan, Jian Yang et al., Vol. 48, No. 3, pp. 197-201, March 2015) prepared the following Figure 1The imidazole-type cross-linked gel adsorbent shown; Xin Kou (Effect of the length and aromaticity of N3-substituent on adsorption performance of imidazolium-based poly(ionic liquids)towards Pd(II), Journal of Hazardous Materials, Xin Kou et al., Vol. 420, No. 126623, July 2021) prepared as shown Figure 2 The imidazole-type cross-linked gel adsorbent shown in FIG. 1 is prepared by Dong Han (A new imidazolium-based polymeric ionic liquid gel with high adsorption capacity for perrhenate, RSC Advances, Dong Han et al., Vol. 6, No. 73, pp. 69052-69059, July 2016). Figure 3 The imidazole-long carbon cross-linked gel adsorbent shown. Although these imidazole cross-linked gel adsorbents have expanded the application of gel adsorbents in metallurgy, wastewater treatment and other fields, they still have certain limitations: (1) poor selectivity, unable to meet the needs of complex metal solutions, and in the stage of adsorbing metal ions, other adsorbents need to be used in combination for multi-stage process operations; (2) poor mechanical properties, unable to meet the requirements of existing processes.
[0006] In view of this, it is necessary to design an improved polyionic liquid gel adsorbent and a method for adsorbing and separating gold, platinum and palladium to solve the above problems. Summary of the invention
[0007] The purpose of the present invention is to provide a polyionic liquid gel adsorbent and a method for adsorbing and separating gold, platinum and palladium. The polyionic liquid gel adsorbent realizes π-π conjugation through an imidazole ring structure fragment on a molecular main chain, ensures the activity of the imidazole ring, and forms a special spatial network structure, so that the polyionic liquid gel adsorbent can adsorb metal ions to a certain extent. On the other hand, the presence of a Cardo structure fragment further changes the displacement of the π-π conjugated plane on the molecular main chain, and realizes the change of the π-π conjugated stacking density, that is, a specific π-π conjugated structure and a special high-stability network structure are formed through the mutual cooperation of the imidazole ring structure fragment and the Cardo structure fragment, so that the polyionic liquid gel adsorbent has the characteristics of high strength, high mechanical properties and high tensile strength while realizing high selective adsorption of metal ions.
[0008] To achieve the above-mentioned object of the invention, the present invention provides a polyionic liquid gel adsorbent, wherein the polyionic liquid gel adsorbent comprises an imidazole ring structure fragment and a Cardo structure fragment; the polyionic liquid gel adsorbent has the following structural formula:
[0009]
[0010] Wherein, R is hydrogen, methyl, ethyl;
[0011] The structural formula of the molecule is:
[0012] 0≤x≤3.
[0013] As a further improvement of the present invention, the adsorption rates of the polyionic liquid gel adsorbent for gold, platinum and palladium are all as high as over 97%; and the tensile strength is as high as 0.57 MPa.
[0014] The present invention also provides a method for separating gold, platinum and palladium by adsorption using a polyionic liquid gel adsorbent, which is carried out using the polyionic liquid gel adsorbent described above, and specifically comprises the following steps: adding the polyionic liquid gel adsorbent to a gold solution, a platinum solution or a palladium solution containing gold, platinum or palladium, and utilizing different ionic forms of gold, platinum or palladium and other coexisting ions in the solution to achieve selective adsorption of gold, platinum or palladium in the solution;
[0015] Gold, platinum and palladium are respectively in the form of AuCl4 - 、PtCl6 2- 、PdCl4 2- Form exists;
[0016] The solution containing gold or platinum is adjusted to pH=1-6, and the solution containing palladium is adjusted to pH=1-5.
[0017] As a further improvement of the present invention, the solution containing gold, platinum or palladium includes ore solution, catalyst waste liquid, metallurgical waste liquid, and electronic waste leaching solution.
[0018] As a further improvement of the present invention, the polyionic liquid gel adsorbent is obtained by polymerization and cross-linking reaction of an olefinic imidazole-type ionic liquid monomer and a cross-linking agent; wherein the cross-linking agent molecular structure contains both a ring structure fragment and a Cardo structure fragment, and the specific molecular structure is as follows:
[0019]
[0020] Among them, 0≤x≤3.
[0021] As a further improvement of the present invention, the structural formula of the alkenyl-containing imidazole-type ionic liquid monomer is:
[0022]
[0023] Among them, R is hydrogen, methyl, or ethyl.
[0024] As a further improvement of the present invention, the preparation method of the polyionic liquid gel adsorbent is radiation polymerization crosslinking, which first induces C=C bonds to generate free radicals, further triggering polymerization and crosslinking between the molecular chains of the ionic liquid monomer and the crosslinker, thereby forming the polyionic liquid gel adsorbent.
[0025] As a further improvement of the present invention, the radiation polymerization cross-linking adopts 60 Coγ-ray, irradiation dose is 10-300kGy; gel fraction is not less than 50%.
[0026] As a further improvement of the present invention, the polymerization cross-linking reaction is carried out in an aqueous solution, ethanol or DMSO solution of an imidazole type ionic liquid with a concentration of 5-80wt%, and the reaction temperature is controlled at 25-85°C.
[0027] As a further improvement of the present invention, the pore size of the polyionic liquid gel adsorbent is 50-1500 μm
[0028] The beneficial effects of the present invention are:
[0029] (1) The polyionic liquid gel adsorbent provided by the present invention realizes π-π conjugation through the imidazole ring structure fragment on the main chain of the molecule, ensures the activity of the imidazole ring, and forms a special spatial network structure, so that it can adsorb metal ions to a certain extent; on the other hand, the presence of the Cardo structure fragment further changes the displacement of the π-π conjugated plane on the main chain of the molecule, realizing the change of the π-π conjugated stacking density, that is, through the mutual cooperation of the imidazole ring structure fragment and the Cardo structure fragment, a specific π-π conjugated structure and a special high-stability network structure are formed, which realizes high selective adsorption of metal ions while having the characteristics of high strength, high mechanical properties, and high fracture strength. In addition, the polyionic liquid gel adsorbent also has good corrosion resistance, which expands the applicable conditions of the material itself, for example, it can be used in a high acid environment.
[0030] (2) The present invention provides a method for separating gold, platinum and palladium by adsorption using a polyionic liquid gel adsorbent. The method is simple to operate and has a high adsorption rate for gold, platinum and palladium, and can efficiently achieve selective adsorption of gold, platinum and palladium. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The molecular structure of imidazole-long carbon cross-linking prepared by Jian Yang.
[0032] Figure 2 Molecular structure of imidazole-long carbon crosslink prepared by Xin Kou.
[0033] Figure 3 This is the molecular structure of imidazole-long carbon cross-linking prepared by Dong Han.
[0034] Figure 4 This is a schematic diagram of the preparation principle of the polyionic liquid gel adsorbent provided by the present invention.
[0035] Figure 5 This is a schematic diagram of the preparation principle of the polyionic liquid gel adsorbent provided in Example 1.
[0036] Figure 6 6a is an experimental analysis diagram of the adsorption and separation of platinum in a solution containing coexisting ions of copper, iron, zinc and nickel by the polyionic liquid gel adsorbent prepared in Example 1; 6b is an experimental analysis diagram of the adsorption and separation of palladium in a solution containing coexisting ions of copper, iron, zinc and nickel by the polyionic liquid gel adsorbent prepared in Example 1; 6c is an experimental analysis diagram of the adsorption and separation of gold in a solution containing coexisting ions of copper, iron, zinc and nickel by the polyionic liquid gel adsorbent prepared in Example 1.
[0037] Figure 7 This is the synthesis route diagram of the cross-linking agent in Example 1. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0039] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0040] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0041] The present invention provides a polyionic liquid gel adsorbent, which comprises an imidazole ring structure fragment and a Cardo structure fragment; specifically, the polyionic liquid gel adsorbent has the following structural formula:
[0042]
[0043] Wherein, R is hydrogen, methyl, ethyl;
[0044] The structural formula of the molecule is as follows:
[0045] 0≤x≤3.
[0046] On the one hand, the polyionic liquid gel adsorbent realizes π-π conjugation through the imidazole ring structure fragments on the main chain of the molecule, thereby ensuring the activity of the imidazole ring and forming a special spatial network structure, so that it can adsorb metal ions to a certain extent; on the other hand, the presence of the Cardo structure fragment further changes the displacement of the π-π conjugated plane on the main chain of the molecule, realizing the change of the π-π conjugated stacking density, that is, through the mutual cooperation of the imidazole ring structure fragments and the Cardo structure fragments, a specific π-π conjugated structure and a special high-stability network structure are formed, which realizes high selective adsorption of metal ions while having high strength characteristics.
[0047] The adsorption rate of the polyionic liquid gel adsorbent for gold, platinum and palladium is as high as over 97%; and the breaking strength is as high as 0.57MPa.
[0048] The present invention also provides a method for separating gold, platinum and palladium by adsorption using a polyionic liquid gel adsorbent, which is carried out using the polyionic liquid gel adsorbent and specifically comprises the following steps:
[0049] The above-mentioned polyionic liquid gel adsorbent is added to a gold solution, platinum solution, or palladium solution containing gold, platinum, or palladium, and the selective adsorption of gold, platinum, or palladium in the solution is achieved by utilizing the different ionic forms of gold, platinum, or palladium and other coexisting ions in the solution. - 、PtCl6 2- 、PdCl4 2- The solution containing gold or platinum is adjusted to pH=1-6, and the solution containing palladium is adjusted to pH=1-5.
[0050] Solutions containing gold, platinum or palladium include ore solutions, catalyst waste liquids, metallurgical waste liquids, and electronic waste leaching solutions.
[0051] The polyionic liquid gel adsorbent is obtained through polymerization and cross-linking reaction of an imidazole-type ionic liquid monomer containing alkenyl and a cross-linking agent.
[0052] Among them, the cross-linking agent molecular structure contains both a ring structure fragment and a Cardo structure fragment, and the specific molecular structure is as follows:
[0053]
[0054] Among them, 0≤x≤3. When x is too high, it will affect the interaction between the Cardo structure fragment and the π-π conjugated plane on the main chain of the molecule to a certain extent, thereby affecting the mutual synergistic effect between the imidazole ring structure fragment and the Cardo structure fragment, and further affecting the adsorption effect of the polyionic liquid gel adsorbent.
[0055] The structural formula of the alkenyl-containing imidazole-type ionic liquid monomer is:
[0056]
[0057] Among them, R is hydrogen, methyl, or ethyl.
[0058] The polyionic liquid gel adsorbent is obtained by cross-linking imidazole-type ionic liquid monomers and cross-linking agents through radiation polymerization. Specifically, the C=C bond is first induced to generate free radicals, which further initiates polymerization and cross-linking between the molecular chains of the ionic liquid monomers and the cross-linking agent, thereby forming the polyionic liquid gel adsorbent. The specific reaction principle is as follows: Figure 4 shown.
[0059] Radiation polymerization cross-linking 60 Coγ-ray, irradiation dose is 10-300kGy; gel fraction is not less than 50%. The polymerization cross-linking reaction is carried out in an aqueous solution, ethanol or DMSO solution with a concentration of 5-80wt% of imidazole type ionic liquid, and the reaction temperature is controlled at 25-85°C. The pore size of the obtained polyionic liquid gel adsorbent is 50-1500μm.
[0060] The present invention is described in detail below through specific embodiments.
[0061] Example 1
[0062] A preparation method of a polyionic liquid gel adsorbent comprises the following steps:
[0063] S1. Figure 5 As shown, imidazole ionic liquid monomer and cross-linking agent were added to 1 mL of deionized water, with the mass concentrations of 80% and 4%, respectively. After ultrasonic dissolution, the uniform solution was poured into a polyethylene bag and sealed after degassing with N2.
[0064] S2. Use electron accelerator to irradiate electron beam, so that vinyl generates active free radicals that can be used for polymerization and cross-linking reaction, inducing polymerization and cross-linking of reactant molecular chains to form polyionic liquid gel. Irradiation conditions: irradiation voltage 10MeV, irradiation dose 80kGy, dose rate 10kGy / pass. The obtained gel is dried at 50°C to constant weight, then soaked in deionized water to remove the sol part, and dried again at 50°C to constant weight. The gel fraction of the obtained polyionic liquid gel adsorbent is 50%.
[0065] Comparative Example 1
[0066] A polyionic liquid gel adsorbent, which has a different structure from the polyionic liquid gel adsorbent prepared in Example 1, and the specific structure of the polyionic liquid gel adsorbent prepared in Comparative Example 1 is:
[0067]
[0068] Comparative Example 2
[0069] A polyionic liquid gel adsorbent, which has a different structure from the polyionic liquid gel adsorbent prepared in Example 1, and the polyionic liquid gel adsorbent prepared in Comparative Example 2 has a specific structure as follows:
[0070]
[0071] Comparative Example 3
[0072] A polyionic liquid gel adsorbent, which has a different structure from the polyionic liquid gel adsorbent prepared in Example 1, and the polyionic liquid gel adsorbent prepared in Comparative Example 3 has a specific structure as follows:
[0073]
[0074] in, for
[0075]
[0076] Comparative Example 4
[0077] A polyionic liquid gel adsorbent, which has a different structure from the polyionic liquid gel adsorbent prepared in Example 1, and the polyionic liquid gel adsorbent prepared in Comparative Example 4 has a specific structure as follows:
[0078]
[0079] in, for
[0080]
[0081] The preparation methods of the polyionic liquid gel adsorbents provided in Comparative Examples 1-4 are substantially the same as those in Example 1, except that the corresponding cross-linking agents need only be replaced.
[0082] The following tests were conducted on the relevant properties of the polyionic liquid gel adsorbents prepared in Example 1 and Comparative Examples 1-4.
[0083] (1) The mechanical properties of the polyionic liquid gel adsorbents prepared in Example 1 and Comparative Examples 1-4 were tested using a SHIMADZUAG-I 1KN electronic general material testing machine. The specific results are shown in Table 1.
[0084] Table 1 Mechanical properties
[0085] Example Tensile strength(MPa) Example 1 0.57 Comparative Example 1 0.07 Comparative Example 2 0.12 Comparative Example 3 0.28 Comparative Example 4 0.32
[0086] As can be seen from Table 1, the tensile strength of the polyionic liquid gel adsorbent prepared in Example 1 is as high as 0.57 MPa. When the structure of the cross-linking agent is changed (Comparative Example 1), the structure of the Cardo fragment in the cross-linking agent is changed (Comparative Examples 2-3), and the structure of the imidazole ring in the cross-linking agent is changed (Comparative Example 4), the performance of the prepared polyionic liquid gel adsorbent is significantly poor, indicating that the mutual synergy of the imidazole ring structure fragment and the Cardo structure fragment can significantly improve the mechanical strength of the material, thereby expanding its application range.
[0087] (2) The polyionic liquid gel adsorbents prepared in Example 1 and Comparative Examples 1-4 were subjected to an adsorption effect experiment in a highly acidic environment system. The specific operation steps are as follows:
[0088] Weigh 10 mg of the polyionic liquid gel adsorbent prepared in Example 1 and Comparative Examples 1-4 respectively, and add 10 mL of AuCl4 - or PtCl6 2- or PdCl4 2- In the aqueous solution, use dilute acid and dilute alkali to adjust the AuCl4 - or PtCl6 2- or PdCl4 2- The pH of the solution varied in the range of 1 to 3, and a static adsorption test was performed. The above adsorption test was performed in a water bath oscillator at 25°C. After 24 hours of adsorption, the clear solution was taken and the concentration of gold, platinum or palladium in the solution was detected by ICP-OES, thereby calculating the adsorption amount (Qe) of the polyionic liquid gel adsorbent.
[0089] Table 2 shows the effect of pH on the adsorption of gold, platinum and palladium by the polyionic liquid gel adsorbents prepared in Example 1 and Comparative Examples 1-4.
[0090] Table 2 Adsorption performance in high acid environment system
[0091]
[0092]
[0093] As shown in Table 2, the polyionic liquid gel adsorbent prepared in Example 1 can efficiently adsorb gold, platinum and palladium, and the adsorption rate under the optimal pH condition is more than 97%, and under high acidity conditions (pH = 1), the material also maintains good adsorption capacity, and the maximum adsorption rate of each metal is significantly higher than that of Comparative Examples 1 to 4. When the structure of the cross-linking agent is changed, for example, the structure of the imidazole ring in the cross-linking agent and the Cardo structure fragment in the cross-linking agent, the adsorption efficiency of the obtained polyionic liquid gel adsorbent is reduced, indicating that the mutual synergy of the imidazole ring structure fragment and the Cardo structure fragment can significantly improve the adsorption performance of the material.
[0094] (3) The saturated adsorption experiment of the polyionic liquid gel adsorbent prepared in Example 1 and Comparative Examples 1-4 was carried out. The specific operation steps are as follows:
[0095] 10 mg of the polyionic liquid gel adsorbent prepared in Example 1 and Comparative Examples 1-4 were respectively added to 10 mL of a series of gold solutions (20-2000 ppm) or platinum solutions (20-800 ppm) or palladium solutions (20-500 ppm) of different concentrations in a water bath oscillator at 25° C. After adsorption for 48 hours, the clear liquid was taken and the concentration of gold, platinum or palladium in the solution was detected by ICP-OES, thereby calculating the adsorption amount (Qe) of the polyionic liquid gel adsorbent.
[0096] The saturation adsorption experimental results of gold, platinum and palladium by the polyionic liquid gel adsorbents prepared in Example 1 and Comparative Examples 1-4 are shown in Table 3.
[0097] Table 3 Saturated adsorption performance
[0098]
[0099]
[0100] As shown in Table 3, the saturated adsorption capacities of the polyionic liquid gel adsorbent prepared in Example 1 for gold, platinum and palladium are 881 mg / g, 430 mg / g and 280 mg / g, respectively, which are higher than those of Comparative Examples 1-4.
[0101] (4) The kinetic adsorption experiment of the polyionic liquid gel adsorbent prepared in Example 1 and Comparative Examples 1-4 was carried out. The specific operation steps are as follows:
[0102] 10 mg of the polyionic liquid gel adsorbent prepared in Example 1 was added to 10 mL of a 100 ppm gold, platinum or palladium solution, and the mixture was reacted within 1-120 min. The clear solution was taken and the concentration of gold, platinum or palladium in the solution was detected by ICP-OES to calculate the gel adsorption amount (Qe).
[0103] The results show that the kinetic adsorption of gold, platinum and palladium by the polyionic liquid gel adsorbents prepared in Example 1 and Comparative Examples 1-4 reaches equilibrium within 4 minutes, and the kinetic adsorption performance is not much different.
[0104] (5) The polyionic liquid gel adsorbent prepared in Example 1 was used to adsorb and separate gold, platinum, and palladium from various coexisting ion solutions. The specific operation steps are as follows:
[0105] A series of mixed solutions containing different concentration ratios of gold or platinum or palladium and copper, iron, zinc, and nickel were prepared. 10 mg of the polyionic liquid gel adsorbent prepared in Example 1 was added to 10 mL of the solution, and after adsorption for 24 hours, the clear solution was taken and the concentration of each metal ion in the solution was detected by ICP-OES to calculate the gel adsorption amount (Qe).
[0106] The adsorption results of the polyionic liquid gel adsorbent prepared in Example 1 on each metal ion in the blend solution are as follows: Figure 6 As shown by Figure 6 It can be seen that the polyionic liquid gel adsorbent has excellent adsorption selectivity for gold, platinum or palladium, and basically does not adsorb other coexisting metal ions.
[0107] It can be seen that the polyionic liquid gel adsorbent prepared by the present invention achieves a qualitative change in material properties through the interaction of factors such as the specific Cardo-containing imidazole anhydride molecular structure, the rigid structure segment and its proportion, so that the obtained gel adsorbent has good mechanical strength while maintaining excellent selective adsorption performance.
[0108] A method for preparing the cross-linking agent in Example 1 is provided below. The synthesis scheme is as follows: Figure 7 As shown, the specific steps include:
[0109] S1. Put 0.5 mol of reactant A into a 3L three-necked round-bottom flask, dissolve A in a mixed solution of 700 mL of DMF and 700 mL of toluene, put 100 g of anhydrous potassium carbonate into the above suspension, heat and reflux, and remove the generated water and toluene by azeotropic distillation. When no more water is produced, remove the excess toluene by distillation. After the above reaction is completed, the system temperature is lowered to 60 ° C, 1.1 mol of reactant B is added, and the system temperature is raised to 150 ° C, and the reaction is carried out for 8 hours. After the reaction is completed, the suspension is put into water while hot to produce a large amount of white powdery crude product. The crude product is first filtered and extracted for purification, then repeatedly washed with water and methanol solution, and vacuum dried to obtain product C with a yield of 87%.
[0110] S2. 0.45 mol of product C, 0.8 mol of potassium hydroxide, 100 mL of ethanol and 200 mL of distilled water were placed in a 3L round-bottom flask, and the suspension was heated and refluxed for 8 days. The solution changed from a suspension to a transparent and clear state, and the reaction was completed. The above solution was filtered while hot to remove impurities. After cooling, the filtrate was acidified with hydrochloric acid to pH = 2-3, and the precipitated white powder was separated by filtration, washed thoroughly with water, and vacuum dried to obtain product D with a yield of 92%.
[0111] S3. Put 0.4 mol of product D into a 3L round-bottom flask, add 1000mL of methanol and 300mL of hydrogen bromide mixed solution, and react for 3h. The reaction is over. Put the above suspension into distilled water while hot, filter, and get a solid. Add it into a 5L three-necked flask, add 1000mL of acetone, 20g of NaBr, and 50g of sodium carbonate, stir evenly, add 1.5mol of raw material E, heat and reflux for 48h, and after the reaction is over, put the suspension into water while hot to produce a large amount of crude product, which is filtered, extracted, and purified to obtain product F with a yield of 62%.
[0112] The preparation method of the cross-linking agent of Comparative Examples 2-4 is substantially the same as the preparation method of the cross-linking agent of Example 1, and only the corresponding raw materials need to be replaced, which will not be described in detail here.
[0113] In summary, the present invention provides a kind of polyionic liquid gel adsorbent and its method for adsorbing and separating gold, platinum and palladium. The polyionic liquid gel adsorbent realizes π-π conjugation through the imidazole ring structure fragment carried on the main chain of the molecule on the one hand, ensures the activity of the imidazole ring, and forms a special spatial network structure at the same time, so that it can adsorb metal ions to a certain extent; on the other hand, the presence of the Cardo structure fragment further changes the displacement of the π-π conjugated plane on the main chain of the molecule, realizes the change of the π-π conjugated stacking density, that is, through the mutual cooperation of the imidazole ring structure fragment and the Cardo structure fragment, a specific π-π conjugated structure and a special high-stability network structure are formed, while realizing the high selective adsorption of metal ions, it has the characteristics of high strength, high mechanical properties and high tensile strength. The method is simple to operate, and has a high adsorption rate for gold, platinum and palladium, and efficiently realizes the selective adsorption of gold, platinum and palladium.
[0114] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A polyionic liquid gel adsorbent, characterized in that: The polyionic liquid gel adsorbent comprises an imidazole ring structure fragment and a Cardo structure fragment; the structural formula of the polyionic liquid gel adsorbent is as follows: Wherein, R is hydrogen, methyl, ethyl; The structural formula of the molecule is: 0≤x≤3。 2. The polyionic liquid gel adsorbent according to claim 1, characterized in that: The adsorption rates of the polyionic liquid gel adsorbent for gold, platinum and palladium are all above 97%, and the tensile strength is as high as 0.57 MPa.
3. A method for separating gold, platinum and palladium by adsorption using a polyionic liquid gel adsorbent, characterized in that: The method is carried out using the polyionic liquid gel adsorbent according to any one of claims 1 to 2, and specifically comprises the following steps: adding the polyionic liquid gel adsorbent to a gold solution, a platinum solution, or a palladium solution containing gold, platinum, or palladium, and utilizing the different ionic forms of gold, platinum, or palladium and other coexisting ions in the solution to achieve selective adsorption of gold, platinum, or palladium in the solution; Gold, platinum and palladium are respectively in the form of AuCl4 - 、PtCl6 2- 、PdCl4 2- Form exists; The solution containing gold or platinum is adjusted to pH=1-6, and the solution containing palladium is adjusted to pH=1-5.
4. The method for separating gold, platinum and palladium by adsorption using a polyionic liquid gel adsorbent according to claim 3, characterized in that: Solutions containing gold, platinum or palladium include ore solutions, catalyst waste liquids, metallurgical waste liquids, and electronic waste leaching solutions.
5. The method for separating gold, platinum and palladium by adsorption using a polyionic liquid gel adsorbent according to claim 3, characterized in that: The polyionic liquid gel adsorbent is obtained by polymerization and cross-linking reaction of an olefin-containing imidazole-type ionic liquid monomer and a cross-linking agent; wherein the molecular structure of the cross-linking agent contains both a ring structure fragment and a Cardo structure fragment, and the specific molecular structure is as follows: Among them, 0≤x≤3.
6. The method for separating gold, platinum and palladium by adsorption using a polyionic liquid gel adsorbent according to claim 5, characterized in that: The structural formula of the alkenyl-containing imidazole-type ionic liquid monomer is: Among them, R is hydrogen, methyl, or ethyl.
7. The method for separating gold, platinum and palladium by adsorption using a polyionic liquid gel adsorbent according to claim 5, characterized in that: The preparation method of the polyionic liquid gel adsorbent is radiation polymerization crosslinking, first inducing C=C bonds to generate free radicals, further initiating polymerization and crosslinking between molecular chains of ionic liquid monomers and crosslinking agents, thereby forming the polyionic liquid gel adsorbent.
8. The method for separating gold, platinum and palladium by adsorption using a polyionic liquid gel adsorbent according to claim 5, characterized in that: The radiation polymerization cross-linking adopts 60 Coγ-ray, irradiation dose is 10-300kGy; gel fraction is not less than 50%.
9. The method for separating gold, platinum and palladium by adsorption using a polyionic liquid gel adsorbent according to claim 5, characterized in that: The polymerization cross-linking reaction is carried out in an aqueous solution, ethanol or DMSO solution of an imidazole type ionic liquid with a concentration of 5-80 wt%, and the reaction temperature is controlled at 25-85°C.
10. The method for separating gold, platinum and palladium by adsorption using a polyionic liquid gel adsorbent according to claim 3, characterized in that: The pore size of the polyionic liquid gel adsorbent is 50-1500 μm.
Citation Information
Patent Citations
Novel acidic ionic liquid and catalytic application thereof
CN108570019A
Polyimidazole ionic liquid based copolymer, and preparation method and application thereof
CN108912269A